5y - 13 = 12
With these you always have to DO THE SAME THING to BOTH SIDES OF THE EQUATION.
You are looking for y. So to get rid of that -13, do the opposite. You ADD 13 to both sides of the equation, and you get:
5y - 13 + 13 = 12 +13
Simplify that a bit and it becomes:
5y = 25
Remember you are still looking for the value of y. You have 5 multiplied by y there. Do the opposite. Divide both sides of the equation by 5, and you get:
5y / 5 = 25 / 5
Left hand side: 5 divided by 5 = 1 and 1 x 5 = 5.
Right hand side: 25 / 5 = 5... so your answer is:
y = 5Chat with our AI personalities
3x-4x=12 that means -x equals 12 so x equals -12
6 +6 = 12
False, 12 x 12 equals 143!JOKES! It actually equals 144!hehe!
Neither of the two is correct. It would be 12 inches equals a foot or 144 inches equals 12 feet.
2